2004
DOI: 10.4314/acsj.v11i3.27570
|View full text |Cite
|
Sign up to set email alerts
|

Use of IPM in the control of multiple diseases in maize: Strategies for selection of host resistance

Abstract: Maize (Zea mays) production in sub-Saharan Africa is constantly threatened by the potential outbreak of multiple foliar diseases such as maize streak, northern leaf blight, gray leaf spot, and rust. Improvement of host resistance to these diseases can provide an important component of integrated pest management (IPM). In this paper, conventional and molecular marker-assisted breeding approaches are reviewed and strategies for improvement of host resistance are presented. Pyramiding of quantitative resistance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Most of these have been or are being addressed in Uganda (Pratt et al 2003). The nematode challenge should be taken more seriously as studies have indicated maize yield losses as high as 50% due to nematode damage (Keetch 1989;Bridge 1994).…”
Section: Introductionmentioning
confidence: 97%
“…Most of these have been or are being addressed in Uganda (Pratt et al 2003). The nematode challenge should be taken more seriously as studies have indicated maize yield losses as high as 50% due to nematode damage (Keetch 1989;Bridge 1994).…”
Section: Introductionmentioning
confidence: 97%
“…The fundamental change in maize breeding in sub-Saharan Africa occurred in the early 2000s with a particular focus on delivering stress-tolerant maize varieties to mitigate the impacts of climate change, especially frequent droughts and complex diseases (Pratt et al, 2004;Bäzinger et al, 2006;Kyetere et al, 2019;Prasanna et al, 2021). The orientation of breeding towards climate adaptation and resilience in the last decade has contributed to the successful development and release of multiple-stress tolerant maize varieties, with significant yield advantages over the marketdominant but obsolete varieties (Setimela et al, 2017;Simtowe et al, 2019;Prasanna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The most effective, environmentally friendly and economically viable method of MSV management is by the use of host plant resistance (Lagat et al, 2008). To date, a gene responsible for conferring resistance to MSV is identified as msv1 (Kyetere et al, 1995;Nair et al, 2015).This gene has been fine mapped (Nair et al, 2015) to chromosome 1 and thus can be a suitable candidate locus for introgression into susceptible germplasm using marker assisted selection (MAS) (Pratt et al, 2003;Nair et al, 2015). One of CIMMYT"s elite inbred lines, CML202, is known to harbor this gene (Welz et al, 1998).…”
Section: Maize Streak Diseasementioning
confidence: 99%